2017
DOI: 10.3390/jof3010006
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Disseminated and Extracutaneous Sporotrichosis: Current Status of a Complex Disease

Abstract: Sporotrichosis is an implantation or inoculation mycosis caused by species of Sporothrix schenckii complex; its main manifestations are limited to skin; however, cutaneous-disseminated, disseminated (visceral) and extracutaneous variants of sporotrichosis can be associated with immunosuppression, including HIV-AIDS, chronic alcoholism or more virulent strains. The most common extracutaneous form of sporotrichosis includes pulmonary, osteoarticular and meningeal. The laboratory diagnosis requires observing yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 80 publications
0
115
0
8
Order By: Relevance
“…In fact, experimental models have shown that the efficiency of the immune response will affect the control of fungal burden [ 23 , 24 , 25 , 26 ]. Similarly, in humans and dogs, the occurrence of lesions with high fungal burdens is usually associated with immunosuppressive conditions, such as malnutrition, use of steroid, and the presence of underlying diseases, especially those that induce immunosuppression, such as AIDS [ 27 , 28 , 29 , 30 , 31 , 32 ]. In cats, Miranda et al [ 7 , 33 ] and Souza et al [ 13 ] have already observed that different immune response patterns determine the intensity of the fungal burden in skin lesions of feline sporotrichosis and that large numbers of fungal cells generally occur in lesions with a poorly organized inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, experimental models have shown that the efficiency of the immune response will affect the control of fungal burden [ 23 , 24 , 25 , 26 ]. Similarly, in humans and dogs, the occurrence of lesions with high fungal burdens is usually associated with immunosuppressive conditions, such as malnutrition, use of steroid, and the presence of underlying diseases, especially those that induce immunosuppression, such as AIDS [ 27 , 28 , 29 , 30 , 31 , 32 ]. In cats, Miranda et al [ 7 , 33 ] and Souza et al [ 13 ] have already observed that different immune response patterns determine the intensity of the fungal burden in skin lesions of feline sporotrichosis and that large numbers of fungal cells generally occur in lesions with a poorly organized inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Sporotrichosis is the most reported and globally distributed subcutaneous mycosis (Bonifaz and Tirado-S anchez, 2017). Although considered endemic in tropical and subtropical countries, sporotrichosis has been increasingly observed in other regions and currently is regarded as an important and emergent disease.…”
Section: Introductionmentioning
confidence: 99%
“…While blastomycosis is endemic to SA, it is uncommon; [71][72][73][74] we estimated 10 cases per year. Sporotrichosis, an implantation mycosis that can also present with pulmonary and disseminated disease in HIV, [58,75] has been implicated in sporadic infections and outbreaks in SA, the latter primarily reported among mineworkers. [59,76,77] We estimated 40 cases of sporotrichosis per year.…”
Section: Resultsmentioning
confidence: 99%